2000
DOI: 10.1002/1096-9861(20001009)426:1<106::aid-cne7>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous intrastriatal and intranigral dopaminergic grafts in the parkinsonian rat model: Role of the intranigral graft

Abstract: The current transplantation strategy in experimental and clinical Parkinson's disease (PD) has been to place nigral dopaminergic grafts not in their ontogenic site (substantia nigra) but in their target area (striatum). Although intrastriatal dopaminergic grafts are capable of reinnervating the striatum, they fail to reinnervate the nigra, which may be an important factor limiting the efficacy of fetal tissue transplantation in parkinsonian patients. We have previously shown that simultaneous intrastriatal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The increase of D2 and D3 receptors in the striatum seems to be normalized at this time point [ 42 ]. It has been suggested that the function of SN also depends on dendritic DA release in the SN [ 46 ]. Interestingly, transplantation of DA neurons in the SN can give rise to a reduction of apomorphine-induced rotation [ 44 ].…”
Section: Human Foetal Dopaminergic Neuronal Graftsmentioning
confidence: 99%
“…The increase of D2 and D3 receptors in the striatum seems to be normalized at this time point [ 42 ]. It has been suggested that the function of SN also depends on dendritic DA release in the SN [ 46 ]. Interestingly, transplantation of DA neurons in the SN can give rise to a reduction of apomorphine-induced rotation [ 44 ].…”
Section: Human Foetal Dopaminergic Neuronal Graftsmentioning
confidence: 99%
“…Until this study, contrasting results have been previously reported concerning functional recovery following intrastriatal or intranigral VM grafts. For instance, while some investigations have reported partial restoration in drug-induced rotation behavior in rodents after intranigral transplantation [ 37 , 106 , 107 , 108 ], only very limited [ 24 , 109 , 110 ] or no [ 111 , 112 ] improvement on more complex tasks have been reported. Similarly, in the case of intrastriatal transplantations, several studies have reported significant improvements in motor performance for simple tests [ 19 , 106 , 110 , 112 , 113 , 114 ] but only limited [ 42 , 44 , 45 ] or no improvement [ 40 , 109 , 115 , 116 , 117 ] in more complex tests, such as the grasping task.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying this arise from the significant innervation of the substantia nigra pars reticulata (SNpr) from the descending striato-nigral fibers. Specifically, it is now recognized that dendritic dopamine release plays a key role in the regulation of striato-nigral input (via D1-receptors), as well as in nigral output [ 111 , 141 , 142 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cell suspensions were fi ltered through a 40-ÎŒm pore cell strainer (BD Biosciences) and counted on a hemocytometer using trypan blue (0.2%; Sigma). Cells were implanted at 21 ± 3 days after lesioning in two sites, the SN and the striatum, as this has been shown to be more effective than single intrastriatal graft alone [24,25]. Coordinates from bregma (according to [23]) were as follows: AP +0.6 mm, L +2.8 mm, V -5.5 mm (from skull surface at bregma) for striatum; and AP -5.3 mm, L +2.2 mm, V -7.5 mm (from skull surface at bregma for SN).…”
Section: Implantation Of Cell Linesmentioning
confidence: 99%